Pengenalan Metode Pembelajaran Desain Grafis Menggunakan CorelDRAW dalam Meningkatkan Kompetensi Multimedia Siswa SMKS Islam Jamiah Al-Aziziyah - Abdul Halim (Yayasan Madinah Al-Aziziyah, 2025)
The benefits of learning using Graphic Design Learning media Using CorelDRAW in Improving Multimedia Competence of Jamiah Islam Al-Aziziyah Vocational School Students aims to identify students' initial level of understanding, carry out structured training, and evaluate the impact of implementing graphic design learning on increasing students' multimedia competence. The approach used is qualitative descriptive involving forty students who took part in intensive training for fifty hours in October 2025. The training material focused on mastering basic and advanced graphic design techniques using CorelDRAW through project-based learning methods, such as creating visual designs in the form of illustrations and graphic compositions. The results of the activity showed a significant increase in students' technical abilities and creativity, which was seen from their success in producing simple design work with a good understanding of the principles of composition, color and layout. The high level of enthusiasm and positive responses from participants shows that this practical learning approach is effective in increasing competence in the field of graphic design. This program provides an empirical contribution to the development of multimedia vocational education, as well as opening opportunities for sustainable collaboration between universities and vocational schools to answer the needs of the creative industry which continues to grow.